ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI INTENSI IMPLEMENTASI E-MONEY DALAM TRANSAKSI USAHA PADA PEDAGANG ASONGAN UNTUK MENINGKATKAN CASHLESS SOCIETY DI BATAM - Han, Diny; Vanomy, Afrianti Elsye (Profit: Jurnal Adminsitrasi Bisnis, 2022)
This study aims to determine the effect of facilities, business expectations, attitudes towards e-money and security towards street vendor. This study uses a sampling method in the form of Non Probability Sampling. The sampling technique used in this study used purposive sampling. Samples taken as many as 100 respondents. The analytical method used in this research is a quantitative analysis method and this research uses data collection method by distributing online questionnaires to street vendor in the city of Batam. This study uses Statistical Product and Service Solutions (SPSS) version 22 for data analysis.The results of this study indicate facilities have no effect on e-money implementation, business expectations have a significant effect on e-money implementation, e-money towards attitudes have a significant effect on e-money implementation. and security do not have a significant effect on the implementation of e-money. Keywords : Street vendor, E-Money, Cashless Society